2019
DOI: 10.1186/s12890-019-1026-0
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation after inhalation of nano-sized zinc oxide particles in human volunteers

Abstract: BackgroundWorkers in the zinc production and processing of galvanized sheet steel are exposed to a complex mixture of particles and gases, including zinc oxide (ZnO) that can affect human health. We aimed to study the effects of short-term controlled exposure to nano-sized ZnO on airway inflammatory markers in healthy volunteers.MethodsSixteen subjects (8 females, 8 men; age 19–42, non-smokers) were exposed to filtered air and ZnO nanoparticles (0.5, 1.0 and 2.0 mg/m3) for 4 h, including 2 h of cycling with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…[ 104 ] To the best of our knowledge, we are aware of only a two sets of experiments that have performed inhalation exposures to a MNM of potentially greater toxicity (excluding combustion‐derived particle studies), both using zinc oxide nanoparticles. [ 105–108 ] Beckett et al. carried out controlled exposure to 0.5 mg m −3 ZnO nanoparticles (≈40 nm count median diameter) in healthy volunteers, and found no effect on subject‐reported symptoms, cardioelectrophysiology (heart rate variability) or blood markers of inflammation or coagulation.…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 104 ] To the best of our knowledge, we are aware of only a two sets of experiments that have performed inhalation exposures to a MNM of potentially greater toxicity (excluding combustion‐derived particle studies), both using zinc oxide nanoparticles. [ 105–108 ] Beckett et al. carried out controlled exposure to 0.5 mg m −3 ZnO nanoparticles (≈40 nm count median diameter) in healthy volunteers, and found no effect on subject‐reported symptoms, cardioelectrophysiology (heart rate variability) or blood markers of inflammation or coagulation.…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%
“…[ 107 ] The exposure also caused airway inflammation and symptoms of irritation, although the effects were not concentration‐dependent. [ 108 ] There was no indication of oxidative stress (F 2α ‐isoprostane levels) in the sputum, but matrix metalloproteinase‐9 (MMP‐9) levels were increased. The findings provided valuable information to inform the setting of occupational levels of zinc nanoparticles.…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a variety of mechanisms, zinc has been suggested as an adjunct for treatment for COVID-19 respiratory infections, [62] mostly due to the observed effect zinc ions have on the RNA polymerase of the corona virus [63]. At the same time, it has been shown that reversible airway inflammation can occur after inhalation of zinc oxide nanoparticles [64].…”
Section: Zincmentioning
confidence: 99%
“…(63) At the same time, it has been shown that reversible airway in ammation can occur after inhalation of zinc oxide nanoparticles. (64)…”
Section: Zincmentioning
confidence: 99%